Solid-state dye-sensitized solar cells based on ZnO nanocrystals. - Boucharef, M; Di Bin, C; Boumaza, MS; Colas, M; Snaith, H; Ratier, B; Bouclé, J (2010)
We report on the development of solution-processed ZnO-based dye-sensitized solar cells. We fabricate mesoporous ZnO electrodes from sol-gel processed nanoparticles, which are subsequently sensitized with conventional ruthenium complexes and infiltrated with the solid-state hole transporter medium 2, 2', 7, 7'-tetrakis-(N, N-di-p-methoxyphenylamine)-9, 9'-spirobifluorene (spiro-OMeTAD). Starting from ZnO nanorods synthesized from solution, we investigate the porous ZnO film morphology using various precursor formulations. The nature of the polymeric additive used in the initial ZnO formulation, as well as the ZnO electrode sintering treatment, is varied and its influence on device performance and charge dynamics, probed by transient perturbation techniques, is discussed. We show that using ethyl-cellulose in the initial ZnO formulation is responsible for an improved dye loading on the ZnO porous electrode, while a gradual sintering step at 350 degrees C is suitable for the proper removal of the organic phases that can be found in the ZnO films after their deposition by spin-coating. Using only 800 nm thick porous ZnO electrodes sensitized by N719, the best performing device exhibits a short-circuit current density of 2.43 mA cm(-2) under simulated solar emission of (100 mW cm(-2)), associated with an overall power conversion efficiency of 0.50%.